REPRESENTASI ETNISITAS DALAM MEDIA: ANALISIS PENGARUH FILM INDONESIA TERHADAP PERSEPSI MASYARAKAT TERHADAP ETNIS TIONGHOA - Purwanto, Eko; Azzahra, Mahnum Elbah; Sari, Dian Nurvita; Ashari, Sulthanah Dzakyah; Saronta, Syahrul (CAKRAWALA: JURNAL HUMANIORA BINA SARANA INFORMATIKA, 2024)
This research is a media study that discusses the representation of Chinese ethnic identity in film. The concept of postcolonial theory is used to dismantle the respresentation of Chinese ethnic identity carrried out by text. The research result show that the media has perpetuated the Chinese identity of discrimination, racism and stereotypes of rich minorities. Film as a tool conveys this meaning, that not all Chinese culture is discriminatory or negative. The aim of this research was to analyze the influence of Chinese ethnicity in society. So, there are no more misunderstandings in the film regarding the attitude and behavior of ethnic Chinese culture. Even though it provides positive benefits, there are challenges related to the Chinese ethnicity, emphasizing the important role of film in society to help maintain Bhinneka Tunggal Ika. Whitout any discrimination or negative response in the future.